2010
DOI: 10.1523/jneurosci.5405-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Alcohol Inhibit BDNF-Dependent GABAergic Plasticity via L-type Ca2+Channel Inhibition in Developing CA3 Hippocampal Pyramidal Neurons

Abstract: Fetal alcohol spectrum disorder (FASD) is associated with learning and memory alterations that could be, in part, a consequence of hippocampal damage. The CA3 hippocampal subfield is one of the regions affected by ethanol (EtOH), including exposure during the third trimester-equivalent (i.e., neonatal period in rats). However, the mechanism of action of EtOH is poorly understood. In CA3 pyramidal neurons from neonatal rats, dendritic BDNF release causes long-term potentiation of the frequency of GABA A recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 37 publications
4
71
0
Order By: Relevance
“…Direct dendritic patch recordings indicated that an impairment of dendritic calcium signaling is responsible for the observed alterations. It is known that alcohol inhibits voltagegated calcium channels in developing hippocampal pyramidal neurons (Zucca and Valenzuela, 2010). The acute effects reported by Zucca and Valenzuela (2010) would have to be maintained in young adult animals several weeks after the end of alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct dendritic patch recordings indicated that an impairment of dendritic calcium signaling is responsible for the observed alterations. It is known that alcohol inhibits voltagegated calcium channels in developing hippocampal pyramidal neurons (Zucca and Valenzuela, 2010). The acute effects reported by Zucca and Valenzuela (2010) would have to be maintained in young adult animals several weeks after the end of alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that alcohol inhibits voltagegated calcium channels in developing hippocampal pyramidal neurons (Zucca and Valenzuela, 2010). The acute effects reported by Zucca and Valenzuela (2010) would have to be maintained in young adult animals several weeks after the end of alcohol exposure. What could be the possible mechanism to explain the long-lasting observed effects?…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ethanol primarily affects neurotransmitter systems other than glutamate. Work from our laboratory recently demonstrated that exposure of neonatal rats to ethanol from postnatal day two to postnatal days four to six (vapor chambers; BAL = 0.02 or 0.18 g/dl) inhibited LTP of the frequency of GABA A -receptor-mediated spontaneous postsynaptic currents in CA3 pyramidal neurons at postnatal days four to six (Zucca & Valenzuela, 2010). Ethanol exposure is thought to produce this effect by blocking the Ca 2+ -dependent retrograde release of BDNF, which is essential for this developmental form of LTP (Zucca & Valenzuela, 2010).…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Work from our laboratory recently demonstrated that exposure of neonatal rats to ethanol from postnatal day two to postnatal days four to six (vapor chambers; BAL = 0.02 or 0.18 g/dl) inhibited LTP of the frequency of GABA A -receptor-mediated spontaneous postsynaptic currents in CA3 pyramidal neurons at postnatal days four to six (Zucca & Valenzuela, 2010). Ethanol exposure is thought to produce this effect by blocking the Ca 2+ -dependent retrograde release of BDNF, which is essential for this developmental form of LTP (Zucca & Valenzuela, 2010). We hypothesize that third-trimester ethanol exposure produces this effect by altering the function of dendritic voltage-gated Ca 2+ channels involved in BDNF release, a possibility that is supported by a recent study with neocortical pyramidal neurons (Granato, Palmer, De Giorgio, Tavian, & Larkum, 2012).…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Of the four ␣1 subunits, Ca v 1.1-Ca v 1.4, neurons mainly express Ca v 1.2 and Ca v 1.3 (3). During brain development, these two subunits participate in various processes such as neuronal survival (4,5), neurite outgrowth (6,7), the maturation of GABAergic synapses (8,9), the positioning of the axon initiation segment (10), and myelination (11). In the mature brain, L-VGCCs are important for long-term potentiation (12) and glutamate receptor trafficking (13,14).…”
mentioning
confidence: 99%